Historisches Epos, Lehrgedicht, Epithalamium. Zu den Res Danicae des Cimbricus Erasmus Michaelius Laetus - Kreuz, Gottfried (Wydawnictwo Naukowe Uniwersytetu im. Adama Mickiewicza, 2009)
C. Erasmus Michaelius Laetus, poet at the court of Frederik II of Denmark, apparently tried to amplify the glory of the king’s wedding in 1572 by composing a series of poems and dedicating them to the most important allies of his country. He wrote a poem, which obviously attempts to combine historical epic and festive celebration with didactic poetry on a very uncommon subject, the art of a butcher. The paper is an attempt to present the poem of C. Erasmus Michaelius Laetus.
Historical epic, didactic poetry, epithalamium. The Res Danicae of Cimbricus Erasmus Michaelius Laetus
Keywords: epic; didactic poetry; poem; art of butcher